Method of Selecting the Speed of Jack Pump Driving Motor Based on Reservoir Flow Rate - Andriy Malyar; Bohdan Kaluzhnyi; Roman Kvit (Energy Engineering and Control Systems)
The sucker-rod oil pumping unit productivity is influenced by lots of factors, including the operation mode of the jack pump electric drive system. Settings of the electric drive system affect the system’s energy indicators, overhaul period and oil production volume. Therefore, an effective operation of oil production units is an important factor influencing the cost of the produced oil. The paper proposes a method of selecting the speed of the driving motor of the jack pump electric drive that allows balancing the sucker-rod oil pumping unit productivity and the reservoir flow rate. The difference between the pump productivity and that of the reservoir is taken as the electric drive system error. The method is based on the criterion of root-mean-square error minimum and takes into consideration the periodically variable nature of the load torque and inertia moment of the electric drive. It can be used to synthesize a control system for the jack pump electric drive for adjusting the operation of the sucker-rod oil pumping unit to different values of the oil inflow.